Ambient‐light‐adaptive image quality enhancement for full‐color e‐paper displays using a saturation‐based tone‐mapping method. Issue 3 (16th April 2018) - Qin, Zong; Chen, Yi‐Wen; Lin, Fang‐Cheng; Hung, Chi‐Mao; Shieh, Han‐Ping David; Huang, Yi‐Pai
Abstract: Full‐color e‐paper displays that have a small color gamut encounter image tone distortions and contour artifacts in high‐saturation regions. To solve these issues, in this paper, we comprehensively measure the colorimetric responses of input image signals and demonstrate that the perceptual colorfulness in terms of chroma abnormally declines when the input saturation is beyond a certain value. Accordingly, saturation‐based tone‐mapping curves are developed to map the abnormal high saturation to the range that the display is able to normally render. By testing several test charts and natural images, the recoveries of the original image tones and the removals of the contour artifacts are experimentally verified. More important, by discussing how to conduct a database of tone‐mapping curves for different ambient lights and utilize the database for an unknown ambient light, the proposed method is proven to be completely ambient light adaptive. Abstract : The perceptual colorfulness of high input saturation is demonstrated to decline abnormally for full‐color electrophoretic displays. A tone‐mapping method is developed to map the high input saturation to the range that the display can normally render. The tone distortions and contour artifacts in high‐saturation image regions are solved.